2012
DOI: 10.1088/0004-637x/759/1/54
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fields From QCD Phase Transitions

Abstract: We study the evolution of QCD phase transition-generated magnetic fields in freely decaying MHD turbulence of the expanding Universe. We consider a magnetic field generation model that starts from basic non-perturbative QCD theory and predicts stochastic magnetic fields with an amplitude of the order of 0.02 µG and small magnetic helicity. We employ direct numerical simulations to model the MHD turbulence decay and identify two different regimes: "weakly helical" turbulence regime, when magnetic helicity incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
99
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 69 publications
(94 reference statements)
14
99
1
Order By: Relevance
“…In subsequent work he stresses that for constant ν (and η), only the case α = 1 can be realized. For nonhelical MHD, this is indeed compatible with simulations [23][24][25], but not for HD [26] nor for helical MHD [3,18]. In this Letter, we argue that the scaling exponent q is not primarily determined by the initial value of α, as suggested by Eq.…”
supporting
confidence: 75%
“…In subsequent work he stresses that for constant ν (and η), only the case α = 1 can be realized. For nonhelical MHD, this is indeed compatible with simulations [23][24][25], but not for HD [26] nor for helical MHD [3,18]. In this Letter, we argue that the scaling exponent q is not primarily determined by the initial value of α, as suggested by Eq.…”
supporting
confidence: 75%
“…Moreover, in [158], it has been shown that, starting from suitable initial conditions which should reflect the production mechanism of a magnetic field from a bubble collision in a first-order phase transition, a Batchelor spectrum E B ∝ k 4 is established after a short time interval and at small wavenumbers. Nevertheless, we can always assume that on very large scales (very small wavenumbers k) the initial spectrum satisfies the above requirements, but that on smaller scales, where the gross of the magnetic energy is stored, it behaves like k 2 .…”
Section: Initial Conditionsmentioning
confidence: 99%
“…Nevertheless, we see that convergence in the results, at least for the most recent work and for the case of helical magnetic fields, seems to have been achieved (see, in particular, Refs. [156,158,159,161,162]). …”
Section: Freely Decaying Turbulent Magnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken at face value, the survival of helical fields to turbulent diffusion may provide rejuvenated credence to pre-galactic mechanisms of large scale field production that produce sufficiently strong helical fields (Field & Carroll 2000;Copi et al 2008;Díaz-Gil et al 2008;Semikoz et al 2012, Tevzadze et al 2012, Kahniashvili et al 2013) because such helical fields could then avoid decay by supernova driven turbulent diffusion over a galactic lifetime in the absence of boundary terms. Although most energy in large scale galactic magnetic fields resides in non-helical toroidal fields, as long as the turbulent decay time for the non-helical field exceeds the linear shear time, we can expect a predominance of non-helical field in a steady state, even without an in situ dynamo to regenerate the poloidal fields: The helical field provides a minimum value below which the toroidal field cannot drop.…”
Section: Helical Field Decaymentioning
confidence: 99%